A Presentation of Cerebritis Secondary to Granulomatosis with Polyangiitis (Wegener). (12th May 2014) - Norman, James; Pande, Ira; Taylor, Timothy; Gran, Bruno
Abstract : Neurological manifestations of GPA are common, most frequently as a peripheral neuropathy. Cerebritis as a principal presentation is extremely rare. We report a patient who presented with subacute progression of ataxia, confusion, and vacant episodes. An MRI of her brain showed bilateral signal abnormalities in the cingulate and superior sagittal gyrus while a staging CT revealed a mass in the right upper lobe of the patient's lung with a satellite nodule. C-ANCA antibodies specific for PR3 at high titres were positive and a diagnosis of GPA was made. The patient was commenced on intravenous methylprednisolone followed by cyclophosphamide and responded well to treatment. GPA is a rare and treatable differential diagnosis for confused patients with acute or subacute neurological features and unusual MRI findings.